Root canal morphology analysis of maxillary permanent first and second molars in a southeastern Turkish population using cone-beam computed tomography - Mustafa Altunsoy; Evren Ok; Bilge Gulsum Nur; Osman Sami Aglarci; Enes Gungor; Mehmet Colak (Elsevier, 2015)
Background/purpose: The aim of this retrospective study was to determine the root and canal morphology of the maxillary first and second molars in a Turkish subpopulation using cone-beam computed tomography (CBCT). Materials and methods: CBCT images of 417 women and 410 men aged 14-70 years were examined. A total of 1158 maxillary permanent first molars and 1305 maxillary permanent second molars were analyzed. The number of root canals and canal configurations were investigated and classified according to Vertucci's classification. The data were analyzed using Pearson's Chi-square test. Results: In both first and second maxillary molars, the presence of three roots was the most common occurrence. The prevalence of additional canals (type II, III, or greater) in mesiobuccal roots of maxillary first and second molars was approximately 62% and 37.5%, respectively. Type I canal configuration was the most prevalent in the distobuccal (99.6%) and palatal (99.8%) roots of maxillary first molars, and in the distobuccal (99.7%) and palatal (99.2%) roots of maxillary second molars. The incidence of the number of root canals and the configurations of maxillary first and second molars did not statistically differ with sex (P > 0.05). Conclusion: The high prevalence of additional canals in the mesiobuccal roots of maxillary first and second molars is noteworthy. CBCT is an effective method to study the external and internal morphology of dental tissues.